Crystal structure of (4-(4-chlorophenyl)-1H-pyrrole-3-carbonyl)ferrocene, C21H16ClFeNO - Li Xiaohua; Dang Xiaolin; Yu Jingyin; Liu Bin (Zeitschrift für Kristallographie - New Crystal Structures)
C21H16ClFeNO, monoclinic, P21/c (no. 14), a = 14.6936(11) Å, b = 9.3784(6) Å, c = 12.7854(8) Å, β = 105.183(2)°, V = 1700.4(2) Å3, Z = 4, R gt(F) = 0.0584 wR ref(F 2) = 0.1719, T = 170 K.